2013
DOI: 10.1007/978-3-642-29578-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Distortion-Free Authentication Watermarking.

Abstract: Abstract. In this paper 1 we introduce a distortion free watermarking technique that strengthen the verification of integrity of the relational databases by using a public zero distortion authentication mechanism based on the Abstract Interpretation framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In recent years, distortion-free database watermarking has been received much attention from researchers. Some pioneer works have been done by incorporating abstract interpretation framework to characterize the approximation of the semantics inside the table [9]- [11], [20]. In this case, the partitioning can be seen as a virtual grouping.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, distortion-free database watermarking has been received much attention from researchers. Some pioneer works have been done by incorporating abstract interpretation framework to characterize the approximation of the semantics inside the table [9]- [11], [20]. In this case, the partitioning can be seen as a virtual grouping.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the other viewpoint, most of the previous studies rely on adding the watermark with some distortion to the database and little of them assign the watermark with distortion free. It was observed that most previous studies that used the distortion-free' characteristics to add a watermark are based on (1) Abstract interpretation framework as a theory of the approximation of the semantics in such a way that semantic meaning of data is preserved [9]- [11]; (2) Permutation -based framework that performs the exchange of tuples' positions based on linear permutation un-ranking algorithm to increase the embedding capacity [1], [12], [13]. (3) Fake (virtual) attribute adding framework that inserts a new column that is not real to the relation as a watermark; or by adding only one hidden tuple with a secret function where its values are known only by the data owner [14]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, found a way of watermark design based on Steiner triple systems [5]. Bhattacharya et al, devised a distortionfree authentication watermark [6]. Khanduja et al, adopted bacterial foraging algorithm to construct a database watermark [7].…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, most of the research works in relational database watermarking focused on the following three main applications regardless of the database attributes type (numeric, nonnumeric, or mix format): database ownership protection, content authentication, and fingerprinting. Usually, the ownership protection and the fingerprinting techniques [1][2][3][4] can be considered as part of robust watermarking approach, whereas the authentication or integrity checking [5][6][7] is based on the fragile watermarking technique. Whether a watermarking scheme is fragile or robust, it may suffer from intentional or unintentional attacks which may destroy the watermark [8].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach is a distortion-free fragile watermarking technique; it does not change any data value from the database. In the literature there is a huge research work on relational database watermarking but only few of them are focused on fragile watermarking technique [7,15].…”
Section: Introductionmentioning
confidence: 99%